Pengaruh Pengungkapan Corporate Social Responsibility terhadap Nilai Perusahaan di Sektor Pertambangan - Evelyn Stacia; Juniarti Juniarti Juniarti (Business Accounting Review, 2016)
This research aimed to identify the affect of Corporate Social Responsibility (CSR) to firm value had been done many times, but the results were inconsitent. The objective of this research was to identify the affect of CSR to firm value in mining sector. CSR was measured by using GRI Index version 3.1 while firm value was measured by Tobin’s Q. The control variables used in this research were firm size, market share, and debt-to-equity ratio (DER). This research used 135 observation sampel during 2009-2013 and tested by SPSS 20. The results of this study demonstrated that corporate social responsibility had no significant affect on the firm value; firm size had significant and negative affect on the firm value; market share had significant affect on the firm value; and debt to equity ratio did not have significantly influence on the firm value.